Seasonal and vertical variations of nutrient cycling in the world’s deepest blue hole - Chen, Lin; Yao, Peng; Yang, Zuosheng; Fu, Liang (Frontiers in Marine Science, 2023)
Nutrient cycling in anoxic seawaters is essential to marine ecosystem health and sustainability, yet it remains poorly understood. In this work, we analyzed dissolved inorganic nutrients as well as hydrochemical parameters in the Yongle Blue Hole (YBH) of the South China Sea in October 2019, which is the world’s deepest blue hole and is characterized by anoxia below the depth of 100 m. Nutrient data collected in two sampling campaigns in 2017 were also incorporated to examine the seasonal and vertical variations of nutrient cycling across steep redox gradients in the YBH. In response to the changes in redox conditions in different seasons, nutrients in the YBH showed significant seasonal variations. The nitrate maximum rose from a depth of 90 m in March 2017 to 60-80 m in October 2019, while the primary nitrite maximum concentration decreased from 0.5 μmol/L to 0.1 μmol/L. In October 2019, the nitrite decreased to below the detection limit at about 100 m, while in March 2017, it was 140 m. The regeneration of phosphate and silicate both started from around 40 m in October 2019 and from 80 m in March 2017. Silicate shows non-conservative adding behaviors relative to phosphate and DIN, and phosphate shows a similar but weaker adding behavior relative to DIN. The nutrient ratios also varied seasonally, especially for N/P, which fluctuated greatly on the surface at 80 m, while Si/N and Si/P fluctuated above 50 m. At the oxic-anoxic interface, extreme values of nutrient ratios were observed, and below 150 m, the N/P, Si/N, and Si/P were kept constant at about 17, 1.5, and 26, respectively. Seasonal and vertical variations of nutrient concentrations and ratios in the YBH reflect the impact of redox conditions on nutrient cycling in anoxic seawaters, especially during the transition from oxic to anoxic zone. And the high-resolution distributions of nutrients and hydrochemical parameters are helpful to better understand the nutrient cycling processes in highly dynamic coastal environments that are suffering deoxygenation.